A review of the role of parasites in the ecology of reptiles and amphibians - Bower, Deborah S.; Brannelly, Laura A.; McDonald, Cait A.; Webb, Rebecca J.; Greenspan, Sasha E.; Vickers, Mathew; Gardner, Michael G.; Greenlees, Matthew J. (Austral ecology, 2019)
A great diversity of parasites, from viruses and bacteria to a range of remarkable eukaryotic organisms, exploit reptile and amphibian hosts. Recent increases in the emergence of infectious disease have revealed the importance of understanding the effects of interactions between hosts and their parasites. Here we review the effects of parasite infection on a range of demographic, behavioural, genomic and physiological factors in reptile and amphibian species. Reviewing these parasite roles collectively, and prioritising areas for research, advances our ecological understanding and guides direction for conservation in a time of rapid species decline. Poorly resolved systems include Gymnophionan amphibians and Crocodilian hosts, in addition to viral and bacterial parasites. Future research should seek to understand processes enabling population recovery and examining synergistic interactions of parasites with fragmentation, climate change and other processes that threaten species persistence. Une grande diversité de parasites, des virus et bactéries à un éventail de remarquables organismes eucaryotes, utilisent des reptiliens et amphibiens comme hôtes. L'augmentation récente de l’émergence de maladies infectieuses ont mis l'accent sur l'importance de comprendre les effets des interactions entre les hôtes et leurs parasites.  Cet article examine les effets des infections de parasites selon un éventail de facteurs démographiques, comportementaux, génomiques et physiologiques chez des espèces de reptiles et d'amphibiens. L’étude des rôles de ces parasites collectivement, et la priorisation de domaines de recherche, améliore notre connaissance écologique et dirige les efforts de conservation en période de déclin rapide des espèces. Certains systèmes mal résolus incluent des hôtes amphibiens de Gymnophion et Crocodilien, en plus de parasites viraux et bactériens. Les recherches futures devront chercher à comprendre les processus permettant le rétablissement des populations et à examiner les interactions synergétiques des parasites avec la fragmentation de leur habitat, le changement climatique, et autres processus qui menacent la persistance des espèces.